Pulmonary hemorrhage in pediatric lupus anticoagulant hypoprothrombinemia syndrome - Ji Soo Kim; Min Jae Kim; E Young Bae; Dae Chul Jeong (Korean Pediatric Society, 2014)
Lupus anticoagulant-hypoprothrombinemia syndrome (LAHPS), a very rare disease that is caused by the presence of antifactor II antibodies, is usually counterbalanced by the prothrombotic effect of lupus anticoagulant (LAC). Patients with LAHPS are treated using fresh frozen plasma, steroids, immunosuppressive agents, and immunoglobulins for managing the disease and controlling hemorrhages. Notably, steroids are the important treatment for treating hypoprothrombinemia and controlling the bleeding. However, some patients suffer from severe, life-threatening hemorrhages, when factor II levels remain very low in spite of treatment with steroids. Here, we report a case of LAHPS in a 15-year-old girl who experienced pulmonary hemorrhage with rapid progression. She was referred to our hospital owing to easy bruising and prolonged bleeding. She was diagnosed with LAHPS that presented with pancytopenia, positive antinuclear antibody, proloned prothrombin time, activated partial thromboplastin time, positive LAC antibody, and factor II deficiency. Her treatment included massive blood transfusion, high-dose methylprednisolone, vitamin K, and immunoglobulin. However, she died due to uncontrolled pulmonary hemorrhage.